Pengaruh Earning Per Share, Current Ratio, Net Profit Margin, Dan Debt To Equity Ratio Terhadap Harga Saham Pada Perusahaan Pertambangan Yang Terdaftar Di BEI Pada Tahun 2018-2022 - Prayitna, Hary; Nyoman Ari Surya Dharmawan (Universitas Pendidikan Ganesha, 2024)
This research aims to analyze the effect of Earning Per Share, Current Ratio, Net Profit Margin, and Debt to Equity Ratio on stock prices in mining companies listed on the IDX in 2018-2022. The type of research used in this research is the causal relationship between variables. This research aims to test the hypothesis proposed to explain the variables. This research uses four independent variables and one dependent variable for go-public companies which is operating in the mining sector on the Indonesia Stock Exchange (BEI) in 2018-2022. The independent variables used are Earning Per Share (EPS), Current Ratio (CR), Net Profit Margin (NPM), and Debt to Equity Ratio (DER), while the dependent variable in this research is stock price. The result of this research states that Earning Per Share (EPS), Current Ratio (CR) and Debt to Equity Ratio (DER) have a significant effect on stock prices simultaneously, while Net Profit Margin (NPM) has no significant effect on stock prices. Keywords: Earning Per Share; Current Ratio; Net Profit Margin; Debt to Equity Ratio; and Share Price